Microalbuminuria as a Predictor of Pre-eclampsia in Pregnant Women Presenting in the Antenatal Clinic at Dhulikhel Hospital - Dongol, A.; Timilsina, N.; Bastakoti, R.; Bhatta, R. D.; Risal, P. (Kathmandu University Medical Journal, 2020)
Background Pre-eclampsia is described as a pregnancy-specific syndrome that can affect virtually every organ system. The appearance of proteinuria remains an important diagnostic criterion. Proteinuria is an objective marker and reflects system-wide endothelial leak, which characterizes the pre-eclampsia syndrome. Objective To determine protein values using the spot urinary albumin/creatinine ratio amongst the pregnant women and to identify whether this test can be used as the investigation of choice for predicting pre-eclampsia in near future. Method A hospital based observational cross-sectional study conducted from February 2016 to August 2017. The study included pregnant women from 20-28 weeks of gestation. They were tested for spot urinary albumin and creatinine. They were all followed up till term, delivery and post partum. Result The mean age of the study patients was 28 years (N+335), the most common age group being 25 to 29 years (43.6%). Pregnant women with higher values of urinary albumin/creatinine ratio were found to develop hypertension compared to women with normal values of urinary albumin/creatinine ratio in the third trimester with insignificant difference (p < 0.283) statistically. Conclusion Microalbuminuria is one of the predictor of pre-eclampsia however it cannot be used as routine investigation for predicting pre-eclampsia in future; further studies in large scales are needed to prove whether urinary albumin/creatinine ratio can be utilized as predictor for pre-eclampsia or not.